Who is Ruth Bader Ginsburg? - Demuth, Patricia; Murray, Jake (New York : Penguin Workshop, 2019)
"Justice Ruth Bader Ginsburg is famous for her stylish collars (called jabots) and her commanding dissents. This opera-loving New Yorker has always spoken her mind; as a young lawyer, RBG advocated for gender equality and women's rights when few others did. She gained attention for the cases she won when arguing in front of the Supreme Court, before taking her place on the bench in 1993. Author Patricia Brennan Demuth answers all the question about what makes RBG so notorious and irreplaceable"--
Who Is Ruth Bader Ginsburg? -- An Immigrant Family -- A Terrible Secret -- Opposites Attract -- Law School -- Changing Times -- Landmark Cases -- From Lawyer to Judge -- "Oyez! Oyez! Oyez!" -- "I Dissent!" -- RBG Today.
"An official WhoHQ book"--Cover.
Includes bibliographical references.
Ages 8-12
Keywords: Ginsburg, Ruth Bader -- Juvenile literature; Women judges -- United States -- Biography -- Juvenile literature; Women judges -- United States -- Biography; Biographies